Strategy for Fortifying the Batursari Kledung Temanggung Village Community from Radicalism and Terrorism - Masyhar, Ali; Aisy, Rohadhatul (Indonesian Journal of Advocacy and Legal Services, 2024)
Central Java, as a reflection of a calm and peaceful society, is disturbed by the rise of terrorism, which has made the region a base for recruitment and terror regeneration. Acts of terror are always preceded by the implantation of radical ideologies. Therefore, preventive efforts are necessary to thwart the spread of these radical ideologies. This activity aims to foster a preventive attitude to counter radical ideologies in the Batursari community, Kledung Sub-district, Temanggung Regency, and to provide recommendations to the government on the necessary actions to ensure legal protection for the Batursari community against terrorism and radicalism. This activity is in partnership with the Ansor Youth Movement (GP) PAC of Kledung Sub-district, Temanggung Regency, which is one of the autonomous bodies of Nahdlatul Ulama. The methods used in this activity include lectures and dialogues, as well as focused discussions. Additionally, brainstorming—collecting opinions from the audience—will be used as an initial effort to gauge their knowledge about terrorism and radicalism. This activity is expected to cultivate a preventive attitude to counter the infiltration of radical ideologies into the community.